Local-level public goods and collective action - McCarthy, Nancy (International Food Policy Research Institute, 2004)
According to the author, Given the vital importance of public goods in providing basic services necessary for alleviating poverty and in managing the local natural resource base for sustainable development, this brief offers an approach to understanding the problems communities face in providing different kinds of public goods. She examines why some public goods are easier to provide than others and why some communities are more successful than others in providing public goods and then explains the implications for policymakers. -- from Text.